Peningkatan Akses Pendidikan Ekonomi untuk Meningkatkan Kemandirian Keuangan di Kalangan Masyarakat Terpencil: Desa Hukurila, Kecamatan Leitimur Selatan, Kota Ambon - Muhammad Bugis; Ali Tutupoho; Fredy H. Louhenapessy; Andre Sapthu; Jani, Jani (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service program aims to improve access to economic education for the people of Hukurila Village, Leitimur Selatan District, Ambon City, with a focus on financial management and the empowerment of small businesses. The majority of the population in Hukurila Village depends on agriculture and fisheries, yet they still face challenges in efficiently managing resources and lack understanding of personal and business financial management. Through a series of training sessions and workshops, this program provides knowledge on financial planning, household budget management, and effective small business management techniques, enabling the community to enhance their economic independence. Additionally, the program introduces simple technologies for financial management and marketing business products, with the goal of expanding market reach for local products. By improving economic literacy and introducing technology, it is hoped that the people of Hukurila Village will be able to manage their finances and businesses more wisely, reduce dependence on external aid, and create sustainable economic independence. This program is expected to serve as a model for economic empowerment in other remote villages, promoting well-being through an inclusive and technology-based approach to economic education.